Ultrathin Polymer Fibers Coated with an Amorphous SiO2–CaO–P2O5 Bioactive Powders for Biomedical Applications - de Siqueira, Lilian [UNESP]; dos Santos, Verônica Ribeiro; de Araújo, Juliani Caroline Ribeiro [UNESP]; de Oliveira Filho, Hugo Gutemberg Patiño [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP]; de Sousa Trichês, Eliandra; Borges, Alexandre Luiz Souto [UNESP] (Springer Nature, 2023)
The development of new biomaterials with improved properties is a trend in tissue regeneration. In this way, an innovative approach is employed in this work for obtaining polymer fibers coated with nanoparticles resulting from the simultaneous application of poly (lactic acid) (PLA)/polycaprolactone (PCL) electrospinning and bioactive particles from an amorphous multicomponent silica–calcium–phosphorus system (AMS) electrospraying. The osteogenesis was evaluated in vitro and in vivo using male rats, in which total protein, alkaline phosphatase, and biological performance through histological and histomorphometric analysis were discussed. The morphological results assessed by scanning electron microscopy showed a mesh of PLA/PCL fibers associated with AMS. The spraying of 17.44% of AMS particles in the PLA/PCL electrospun fibers decreased the Young’s modulus and tensile strength. However, the amount of AMS particles sprayed was enough to promote a reduction of 17.8% in the measured contact angle values. Phosphatase alkaline higher mean value was also observed in the fibers when in contact with the AMS, but nonstatistical difference was observed (p > 0.05). It was possible to observe the presence of mineralized nodules deposited on the bottom of the plate and between the fibers. The newly formed bone into defect filled with PLA/PCL-AMS fibers was higher than that observed in the control group. These findings suggest PLA/PCL-AMS fibers as a multifunctional composite system that may be attractive for both bone and dental tissue engineering applications.
Keywords: Bioactive particles; Biocompatible polymers; Electrospinning/electrospraying; Regenerative medicine